2020
DOI: 10.1038/s41598-020-59892-6
|View full text |Cite|
|
Sign up to set email alerts
|

Antigenic cross-reactivity between Schistosoma mansoni and allergenic invertebrates putatively due to shared glycanic epitopes

Abstract: previous studies have shown that rabbit igG antibodies against Schistosoma mansoni egg antigens (SmSEA) cross-react with allergens in natural rubber latex, peanuts and grass and tree pollens. Here we describe antigenic molecules that cross-react with rabbit anti-S. mansoni igG antibodies in extracts of the house dust mite (HDM) Dermatophagoides farinae, the Australian cockroach (ACR) Periplaneta australasiae and in the venom of the honey bee Apis mellifera (HBV). tandem mass spectrometry identified the cross-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 97 publications
1
5
1
Order By: Relevance
“…However, none of the subjects presented any cutaneous sensitization against common respiratory allergens or clinical symptoms of allergy. In contrast to El-Faham et al's report [24], our analysis of molecular IgE sensitization allows us to suggest that CCD cross-reactivity is not the unique mechanism of allergen sensitization during helminth infection, and that sensitization against peptidic epitopes occurs.…”
Section: Proteic Componentscontrasting
confidence: 89%
See 1 more Smart Citation
“…However, none of the subjects presented any cutaneous sensitization against common respiratory allergens or clinical symptoms of allergy. In contrast to El-Faham et al's report [24], our analysis of molecular IgE sensitization allows us to suggest that CCD cross-reactivity is not the unique mechanism of allergen sensitization during helminth infection, and that sensitization against peptidic epitopes occurs.…”
Section: Proteic Componentscontrasting
confidence: 89%
“…The IgE Dpt and Asc level were not affected by the Phl p 4 depletion, confirming results from Hamid et al who showed that IgE targeting core β-1,2-xylose and/or α-1,3-fucose substituted N-glycans does not play a role in Dpt and Asc sensitization [23]. However, N-glycans are not unique CCDs, and other carbohydrate species may exist in Dpt extract [24].…”
Section: Sensitization To Ccdssupporting
confidence: 82%
“…In this research, the structures of Scy p 1 and Scy p 3 mutants were altered, and the increased surface hydrophobicity could expose more hydrophobic regions on the allergen surface, resulting in the embedding of epitopes within the molecule, thus reducing IgE-binding capacity . Furthermore, disulfide bonds, glycosylation sites, and calcium-binding sites could affect the allergenicity of allergens. ,, Scy p 3 as a member of the EF-hand family that contained calcium-binding sites also had a pair of intermolecular disulfide bonds (Cys36–Cys130) that maintained spatial structure stability and a glycosylation site N 99 G 100 T 101 on the sequence. Thus, the IgE-binding capacity of Scy p 3 mutants (C36A, D66A, and N99A) significantly decreased compared to other mutants, mainly due to particular sites on the structure.…”
Section: Discussionmentioning
confidence: 93%
“…Another important potential source of false-positive results in conventional serological methods caused by CCDs is the occurrence of a high level of cross-reactivity between parasite-and plant-derived glycans recognized by IgG, as shown for Schistosoma mansoni in several studies by Michael J. Doenhoff and his co-workers (El-Faham et al 2020;Igetei et al 2017Igetei et al , 2018. However, the relevance of these findings for IgE responses has yet to be examined.…”
Section: Humanized Ige Reporter Systems Are Extremely Sensitivementioning
confidence: 99%